Implementación de un sistema automatizado de control de variables ambientales de temperatura y dosificación de agua en la crianza de pollitas ponedoras en la Empresa Avícola Ecuatoriana AVESCA C.A. - Malliquinga Tenezaca, Rene Roberto (2017)
In Ecuador, one of the most consumed animals, both in their direct form and in their derivatives, is poultry; the statistics prepared by CONAVE indicate that in our country there are around 230 million broilers and 9.5 million layers in production which supplies the 100% of the national market. Chickens, hens and eggs are present in most households. In the field, the breeding is carried out in an artisan way and in certain cases it is technified to optimize the resources involved and to improve the productive processes. Poultry companies, when handling a higher volume of production, have the need to technify the breeding process in order to avoid losses, optimize resources and manage data in real time of production, always maintaining the comfort of the birds, which is reflected in better production. A person cannot give immediate response and control to factors such as temperature, humidity, water dosage, by the massive amount of birds under care; automation allows efficiency and effectiveness together with an immediate response to maintain the proper conditions they require within the sheds The control of temperature and humidity must be linked because they are proportional; the temperature must be the ideal with respect to the age of the layers to avoid stress levels and to maintain the comfort, besides to avoid diseases by abrupt changes in the environment that can even lead to the death of baby chickens. Also the dosage of water must have a constant flow inside the process of raising the layers, since the water is present in their bodies around 75%; for this reason they must have quality water for their optimum development. With this background, an automatic process is implemented which allows the operation of the variables from a control point by means of the transducer and controller actuator sensors, to quantify them to analyze them, or to keep them according to the situation. In this way, a higher yield of the factors involved is achieved, maintaining the conditions of comfort and well-being for the birds through an immediate response to the temperature variations, which reduces the expense for the control of climatic diseases and reduces the rates of mortality of the chicks.